BiOX™: a new material for industry - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2005)
BiOX™ is a new type of bismuth oxide nanoparticle with distinctive bright orange colour. Its chemical The symbol is Bi2O3 and its molecular weight is 466. The material particle size is 37nm with its corresponding specific surface area of8.9m2g-1. The oxides are of tetragonal ß-Bi2O3 which through controlled synthesis procedure produce materials resemble into rosette morphology. The preparation method opted was rather simple and distinguished by monophase composition of the product, ecological safety and simple operation, therefore promise low operating cost.